PENTINGNYA GAYA KEPEMIMPINAN KEPALASEKOLAH TERHADAP PENINGKATAN KINERJA GURU SD NEGERI MEDONO - Ima Puji Astuti; Noor Miyono (STKIP Subang, 2023)
The problem of the principal's leadership style in improving teacher performance in order to advance the quality of education is a problem that must be addressed. Solving this problem will be followed by a positive impact on the surrounding community, including at the Medono State Elementary School, Boja District, where the principal also uses a leadership style to improve teacher performance that is appropriate to the conditions in the environment. This research uses a qualitative method with a descriptive approach. The author obtained data by conducting observations in the field and conducting in-depth interviews with sources relating to the leadership style of school principals in improving teacher performance at the Medono State Elementary School, Boja District. The conclusions obtained in this research are first, the principal's leadership style in improving teacher performance at the Medono State Elementary School, Boja District uses a participatory leadership style. Second, the performance shown by teachers is still low. Third, the relevant leadership style used by the principal of SDN Medono, Boja District in improving teacher performance is a participatory leadership style coupled with better supervision by the principal of teacher performance. The implication of this research is that the principal's leadership style in improving teacher performance needs to be improved to improve the quality of student education in the Medono State Primary School, Boja District. If the style used by the principal improves, it can be ensured that teacher performance will also increase, thus having an impact on the quality of education produced.